Women's recall of health care provider counselling on gestational weight gain (GWG): a prospective, population-based study - Angela Vinturache; Anika Winn; Cynthia Mannion; Suzanne Tough (BMC, 2019)
Abstract Background Prenatal care has been validated to provide medical and educational counselling intended to reduce the risk of adverse pregnancy conditions and improve the maternal and fetal outcomes. Prenatal targeted information regarding nutrition, lifestyle, and weight gain is predictive of meeting Institute of Medicine (IOM) 2009 gestational weight gain (GWG) guidelines. There is limited information about women's experiences with these prenatal counselling domains, particularly in women who do not meet GWG recommendations. The objective of this study was to evaluate the impact of women's recall of prenatal counselling and its effect on meeting their GWG within guidelines in a prospective, community-based pregnancy cohort. Methods A sample of 2909 women with singleton pregnancies was drawn from the prospective community-based pregnancy cohort All Our Families from Alberta, Canada. Women were stratified into three GWG groups, adequate, inadequate, and excessive GWG, based on pre-pregnancy BMI and the adherence to the Institute of Medicine weight gain in pregnancy guidelines. At less than 25 and 34 to 36 weeks' gestation, maternal socio-demographic information and women's recall of prenatal counselling experiences was collected through self-administered questionnaires. Multivariate logistic regression analyses tested GWG strata impact on women's recall of the prenatal counselling advice in eight domains of nutrition, lifestyle, and weight management during pregnancy. Results Adequate GWG was reached by 35.9% of women, 46.5% gained excessive and 17.6% gained inadequate weight. Women who were overweight and obese prior to pregnancy were more likely to gain excessive weight than women who were normal weight (OR 3.3, 95% CI 2.6-4.1; and OR 2.9, 95% CI 2.1-3.9, respectively). Most women reported having no difficulties in finding prenatal care, felt comfortable with their health care provider and were satisfied with the answers received. There was no difference in the recall of prenatal advice received in any of the eight domains of prenatal counselling assessed among women with appropriate and non-optimal GWG. Conclusion Women with adequate and non-optimal GWG received comparable prenatal counselling on nutrition, weight gain, and lifestyle modifications. There remain missed opportunities in targeting prenatal counselling advice to women at risk for suboptimal or excessive GWG.